Friction and wear maps of copper metal matrix composites with different iron volume content. (April 2019) - Zhou, Haibin; Yao, Pingping; Xiao, Yelong; Fan, Kunyang; Zhang, Zhongyi; Gong, Taiming; Zhao, Lin; Deng, Minwen; Liu, Chao; Ling, Pan
Abstract: Mapping friction and wear behaviours as a function of material composition and operating conditions is a valuable tool, assisting in material selection for component design. The friction and wear maps of copper matrix composites (Cu-MMCs) with different Fe content, tribo-evaluated with different braking energy density (BED) against a steel counterpart, were constructed in this study. According to the friction and wear maps, as well as the wear mechanism map established, Cu-MMCs containing iron volume content ranged from 10% to 15%, exhibited stable high coefficient of friction, associated with low wear rates. Wear mechanisms of Cu-MMCs were distinguished in different regions, which were adhesion, plough, oxidation delamination, severe plastic deformation and delamination. Highlights: Tribological behaviour of Cu-MMCs with different Fe content was investigated. Three-dimensional friction and wear maps have been constructed. Five different main wear mechanisms have been distinguished. The wear mechanism map was developed by analyse of wear rate and wear mechanisms.